The analysis of religious crisis - Tomczyk, Marek (Studia Psychologica: Theoria et praxis, 2007)
The present article constitutes an attempt of psychological analysis of religious crisis. It describes phenomenon of religious crisis, the reasons, circumstances, components and function of crisis in personality development. In order to picture this phenomenon same examples of religious crises experienced by the Saints were include. Religious crises are experience on the natural and supernatural levels. In every case personality is subject to reorganization. The crises are the way leading to God. Sometimes this way is crooked, difficult and full in dramas. The crises don’t select. It is common phenomenon in the world.